Cognitive impairment in multiple sclerosis: diagnosis and monitoring - Meca-Lallana, Virginia; Gascón-Giménez, Francisco; Ginestal-López, Ricardo C.; Higueras, Yolanda; Téllez-Lara, Nieves; Carreres-Polo, Joan; Eichau-Madueño, Sara; Romero-Imbroda, Jesús; Vidal-Jordana, Ángela; Pérez-Miralles, Francisco (Neurological sciences, 2021)
Introduction Cognitive impairment (CI) has a prevalence of 45–70% in people with multiple sclerosis (MS), producing a negative impact on their quality of life, personal life, and work. Early detection of CI has become an important aspect to be considered for an adequate follow-up, to optimize social adaptation and to implement specific cognitive rehabilitation strategies. The aim of this work is to propose a suitable cognitive evaluation of patients with MS based on available and efficient tools for diagnosis and monitoring purposes well supported by literature review and clinical experience. Methods A multidisciplinary panel of professionals from the field of neurology, neuropsychology, and neuroimaging performed a literature review of the topic of cognitive impairment assessment. This was combined and completed with their clinical experience to produce a set of recommendations. Results Some limitations to cognitive evaluation are described: shortage of time and resources during the neurology consultation, scarceness or absence of specialized professionals’ availability, importance of tests adaptation, and doubts about its use to define therapeutic efficiency. We recommend a baseline and annual screening evaluation, and we suggest a baseline and periodic neuropsychological assessment. The latter ought to change to a recommendation with the presence of either positive screening test, or subjective to cognitive complaints, screening-test results and patient or family report mismatch, or in specific social/work situations. Conclusions Cognitive evaluation should be performed on all patients diagnosed with MS and throughout follow-up. It is necessary to support the creation of multidisciplinary MS teams to optimize the evaluation and follow-up of MS patients.